High-throughput sequencing metabarcoding and network analysis elucidate the effects of soil fumigation and biostimulant on potato yield, rhizoctonia canker, and fungal community - Tekeu, Honoré; D’Astous-Pagé, Joël; Jeanne, Thomas; Hogue, Richard (Frontiers in Soil Science, 2025)
This study investigated the impact of chloropicrin fumigation and a Bacillus species-based biostimulant applied alone or in combination in soil of potato crop over five key time-points in season. Rhizoctonia canker incidence, potato yield and the effect on the fungal community have been monitored. Quantitative PCR and high throughput metabarcoding sequencing were used to assess soil fungal diversity, specifically biomass, richness, composition and network interactions. Potato gross yield increased by 7.06% (23.5 cwt. acre-1) with fumigation alone and by 8.41% (28 cwt. acre-1) with biostimulant applied to fumigated soil in comparison to non-fumigated control treatment. Net yield losses caused by rhizoctonia canker exceeded 20% in control plots, while both treatments reduced rhizoctonia canker index by 30% and yield losses to less than 5.6%. Fumigation alone reduced fungal abundance during the season, but the biostimulant slightly increased the mean and variability of fungal abundance. Shannon and Evenness diversity indices decreased in fumigated plots, while the biostimulant increased the variability of Chao1 and Observed ASVs indices throughout the season. Biostimulant application promoted rapid late−season fungal recolonization, enlarged connectivity among taxa in non−fumigated soil, and, when combined with fumigation, eliminated the late−season resurgence of Rhizoctonia solani detected in fumigation−only plots. Fumigation also delivered early-season knock-downs of Fusarium spp. (10-fold reduction) and Colletotrichum coccodes (≥3-fold), yet these both opportunists partially rebounded by harvest while the biostimulant had little effect on these genera. Alternaria spp. and Verticillium nubilum stayed sporadic (<0.5 % reads) but were consistently lowest in fumigated soils. Overall, integrated fumigant–biostimulant management delivered the greatest season−long suppression of pathogenic fungi, the most resilient and functionally connected fungal network, and the highest tuber yield, demonstrating that coupling targeted chemical fumigation with microbial stimulation can reconcile disease control with soil microbiome monitoring in intensive potato systems.